THE EFFECTS OF PHYTASE SUPPLEMENTATIONS IN PREDICTING THE NON-PHYTATE PHOSPHORUS REQUIREMENT OF BROILERS IN STARTER PHASE - Rateh Wulandari; Ferry Poernama; Zuprizal Zuprizal; Nanung Danar Dono (Faculty of Animal Science, Universitas Gadjah Mada, 2017)
This study was aimed to observe the requirements of non-phytate phosphorus (NPP) with phytase supplementation in starter phase broiler. A total number of 1000 broiler (500 males and 500 females) were divided into 5 dietary treatments for 21 days rearing period. The treatment diets (P1-P5) were basal diets with 0.67% Calcium (Ca) and 60 FTU phytase that combined with NPP at different levels, i.e.: 0.420% (P1); 0.345% (P2); 0.270% (P3); 0.195% (P4); 0.120% (P5). The basal diet was a corn-soybean based diet that contained 0.097% Ca and 0.124% Phosphorus (P). The data were subjected to a one-way ANOVA using complete randomized design. Response variables that observed in current study were: feed intake, nett gain, feed convertion ratio, average body weight, mortality and toe ash. Measurement of responses due to the reduction of NPP supplementation on average body weight and toe ash were then followed subsequently by generating equation for quadratic curve y = ax2+bx+c to determinate the NPP requirement. Determination of the maximum response was done through ymaks = -b/2a. Results showed that based on average body weight, estimation of NPP requirement with phytase supplementation were 0.317% for the 0-10 days; 0.314% for the 11-21 days; and 0.315% for the the 0-21 days rearing periods. Based on toe ash content, estimation of NPP requirement with phytase supplementation was 0.990% (toe) for the 21 days rearing period. This study was aimed to observe the requirements of non-phytate phosphorus (NPP) with phytase supplementation in starter phase broiler. A total number of 1000 broiler (500 males and 500 females) were divided into 5 dietary treatments for 21 days rearing period. The treatment diets (P1-P5) were basal diets with 0.67% Calcium (Ca) and 60 FTU phytase that combined with NPP at different levels, i.e.: 0.420% (P1); 0.345% (P2); 0.270% (P3); 0.195% (P4); 0.120% (P5). The basal diet was a corn-soybean based diet that contained 0.097% Ca and 0.124% Phosphorus (P). The data were subjected to a one-way ANOVA using complete randomized design. Response variables that observed in current study were: feed intake, nett gain, feed convertion ratio, average body weight, mortality and toe ash. Measurement of responses due to the reduction of NPP supplementation on average body weight and toe ash were then followed subsequently by generating equation for quadratic curve y = ax2+bx+c to determinate the NPP requirement. Determination of the maximum response was done through ymaks = -b/2a. Results showed that based on average body weight, estimation of NPP requirement with phytase supplementation were 0.317% for the 0-10 days; 0.314% for the 11-21 days; and 0.315% for the the 0-21 days rearing periods. Based on toe ash content, estimation of NPP requirement with phytase supplementation was 0.990% (toe) for the 21 days rearing period.